A Study to Assess the Existing Hand Washing Practices with Soap and Water Among Women at Critical Times in Selected Families of (Kitte 1-7) Field Practice Area of Community Medicine, SGRD, Vallah, Amritsar - Kulwinder Kaur (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Handwashing is the most important thing to prevent and control the illness and avoid the spread of disease. There is greater need regarding awareness of handwashing at critical times to reduce the prevalence of infections and from communicable diseases. However, there is a proper method to ensure all bacteria are removed. It is a technique of rubbing the hands together for a given period of time with soap and water. A study was conducted to assess the knowledge of the women regarding handwashing at community area of SGRD, Vallah, Amritsar, Punjab with the objective: to assess the existing hand hygiene practice of women with soap and water, to find association between sociodemographic variables and existing hand hygiene practices at critical times according to Centers for Disease Control and Prevention guidelines. In this research study, the investigator did an extensive review of the research and non-research literature through reports, thesis, journals, textbooks, and electronic database. The study involved descriptive survey design using non-experimental approach, with convenient sampling technique. The results were calculated using descriptive as well as inferential statistics. Tool consists of two parts: PART A: Sociodemographic variables including age (in years), marital status, education, occupation, income (monthly), dietary habits and PART B: including handwashing questionnaire for women consisting of 10 questions. The study was conducted on 500 women after taking consent from them. On analysis, it was found that majority of women who always wash their hands with soap and water before eating meals were 342 (68.4%). The number of women who always wash their hands before and after caring sick person 305 (61%). Majority of the participants who always wash their hands with soap and water a before and after treating the wound was 327 (65.4%). Same studies can be done on every woman present anywhere to generalize the findings. An experimental study can also be carried further with control group for effective comparison among the two groups.
Keywords: Handwashing; communicable diseases; critical times; sociodemographic variables; women